STRATEGI PENGEMBANGAN KEBUN KOPI KARANGANYAR BLITAR DALAM DIGITAL SUSTAINABLE TOURISM - Anisa Adinda Rahma; Praja Firdaus N (Halu Oleo University, 2025)
This study aims to determine the development strategy of the Karanganyar Blitar Coffee Plantation in digital sustainable tourism. This study uses a descriptive qualitative approach. This study involves in-depth interviews, participatory observation, and documentation. Data analysis was carried out interactively and cyclically, including three main stages: data reduction, data presentation, and conclusion drawing (Miles & Huberman, 2014). The results show that the development strategy of the Karanganyar Coffee Plantation within the framework of digital sustainable tourism successfully integrates digital technology into agrotourism practices as a whole, from production, environmental management, to tourism promotion. The application of computer vision in the harvesting process, the use of Internet of Things (IoT) devices for pest control, and the optimisation of social media in marketing have proven effective in increasing production efficiency, expanding the reach of the tourism market, and strengthening the sustainability of the local ecosystem.